PRAYING TOWARDS AL-AQSA MOSQUE: A STUDY ON MUSLIM CLASSICAL SOURCES - Omar, Abdallah Marouf (Journal of Al-Tamaddun, 2017)
Prayer is the second pillar of Islam after the testimony of faith. It is the only obligation that all Muslims must perform on a daily basis, regardless of financial, health, work, or other status. As the first Qiblah (direction of prayer) of the Muslims, al-Aqsa Mosque and Bayt al-Maqdis obtain special holiness for Muslims that continues to affect the situation in that region today. This article investigates the classical Islamic references’ views on two main aspects that shaped the relationship between Muslim prayer and al-Aqsa Mosque. Namely, the duration of this relationship in the lifetime of the Prophet Muhammad, and the alteration of Qiblah from Bayt al-Maqdis to Makkah. This article concentrates mainly on the standard historical and exegetical traditions, since these kinds of classical sources are considered the main sources on which other historical literature on Bayt al-Maqdis, such as the books of Fada’il (virtues) rely. Indeed, identifying the nature and length of this relationship is important, as contemporary Muslims continue to refer to al-Aqsa Mosque in Bayt al-Maqdis as their first Qiblah, even though their main relationship in prayer is with the Ka‘bah in Makkah. The reasons for changing the direction of prayer to Makkah have been widely discussed in classical Muslim sources. However, major questions that should have been answered in this context have not been tackled in most of these classical sources. This article studies this issue as was elaborated in Muslim classical sources. It reveals that the Prophet Muhammad prayed towards al-Aqsa Mosque in his lifetime for more than 14 years, a longer period than he prayed towards the Ka‘bah. This shows an extensive importance of al-Aqsa Mosque and Bayt al-Maqdis that has been built within Islamic thought since the beginning of Muhammad’s Prophethood.